PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020 - Elizabet Frisley Sibarani; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine and analyze the effect of capital structure and profitability on stock prices in automotive and component companies listed on the Indonesia Stock Exchange in 2016-2020 partially and simultaneously. Where the independent variable in this study is the capital structure and profitability while the dependent variable is the stock price. The sampling technique used was purposive sampling technique and obtained as many as 7 companies. The data in this study uses secondary data, namely financial statements. The data analysis used is financial ratio analysis, descriptive statistical test, multiple linear regression analysis test, coefficient of determination test, and hypothesis testing using SPSS 24. From the results of the analysis of hypothesis testing, both partially and simultaneously, it shows that the capital structure and profitability variables have an influence on stock prices in automotive and component companies listed on the Indonesia Stock Exchange in 2016-2020.Keywords: Capital Structure, Profitability and Stock Price